State of tourism development and directions of state regulation of tourism policy in Ukraine - Viktoriya Khudaverdiyeva (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2022)
The article is devoted to the current problems of the state's tourism industry, their impact on the state of the state's economic development, and the main aspects of improving the state's economy management mechanisms in the context of the development of the tourism industry are defined. For most countries of the world, 2020 will be remembered as the year of the outbreak of the pandemic, which appeared as a result of the spread of the acute respiratory disease COVID-19. Modern tourism, without a doubt, integrates almost all industries. Tourism is definitely one of the highly profitable industries. Tourism forms up to 10% of the total GDP of EU countries. In the developed countries of the world, tourism contributes to the socio-economic development of countries. The purpose of this work is to consider the essence of tourism as a socio-economic phenomenon and the peculiarities of its development in Ukraine. Such features of tour operating require significant organizational skills from the top management of the company, and the ability to effectively work process in the company. Therefore, the activity of a tourist operator is a natural combination of work cycles in relation to specific tours or programs. The article identifies the importance of the hospitality and tourism industry, which is a vital source of income due to tourism revenues and the attraction of foreign direct investment, as well as jobs, especially for women and youth. The start of hostilities on the territory of Ukraine, the closure of external and internal borders in February 2022, not only reduced the revenues of tourism companies to zero, but also led to significant losses in some cases. The Organization for Economic Cooperation and Development (OECD) predicts an unprecedented crisis and a reduction in tourism revenues in the world up to 45%, if the conflict continues until September, this indicator may reach 70%. Since the field of tourism is an important part of the economy of many countries, this will lead to a negative impact on the macroeconomic indicators of the countries in which the field of tourism is the most developed. Many countries have taken decisive measures to support the tourism sector, but this may not be enough to restore the tourism sector. One of the main goals is to support tourism companies and their employees.